Japan : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Macroeconomic policy support and structural reforms have helped to bring about the economic recovery in Japan. Initiating a public process to obtain consensus on a credible strategy for eventual fiscal consolidation would help to raise confidence in long-term growth prospects and reduce the risks of volatile financial market conditions. A premature appreciation of the yen not justified by improving fundamentals remains a concern. Important progress has been made in strengthening major banks balance sheets and allaying concerns about financial instability.